Development of Highly Stable Low Ni Content Catalyst for Dry Reforming of CH4‐Rich Feedstocks. Issue 6 (27th January 2020) - Ha, Quan Luu Manh; Lund, Henrik; Kreyenschulte, Carsten; Bartling, Stephan; Atia, Hanan; Vuong, Than Huyen; Wohlrab, Sebastian; Armbruster, Udo
Abstract: Highly active and coking‐resistant Ni catalysts suited for the dry reforming of CH4 ‐rich gases (70 vol %, e. g. biogas or sour natural gas) were prepared starting from a Mg‐rich Mg−Al hydrotalcite support precursor. Calcination at 1000 °C yields two phases, MgO and MgAl2 O4 spinel. Complexation‐deposition of Ni with citric acid on the preformed support as well as lanthanum addition yields a catalyst with remarkably low carbon accumulation over 100 h on stream attributed to both high Ni dispersion and preferred interactions of Ni with MgO on MgAl2 O4 . Abstract : Dry reforming of methane : Proper thermal pretreatment of MgO−Al2 O3 mixed oxides and impregnation with only 2.5 wt % Ni, in some cases together with citric acid and La, provides Ni catalysts with outstanding stability against coking at severe CH4 ‐rich conditions.